Mediating Roles of PPARs in the Effects of Environmental Chemicals on Sex Steroids - Qiansheng Huang; Qionghua Chen (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) are ligand-activated nuclear receptors that are widely involved in various physiological functions. They are widely expressed through the reproductive system. Their roles in the metabolism and function of sex steroids and thus the etiology of reproductive disorders receive great concern. Various kinds of exogenous chemicals, especially environmental pollutants, exert their adverse impact on the reproductive system through disturbing the PPAR signaling pathway. Chemicals could bind to PPARs and modulate the transcription of downstream genes containing PPRE (peroxisome proliferator response element). This will lead to altered expression of genes related to metabolism of sex steroids and thus the abnormal physiological function of sex steroids. In this review, various kinds of environmental ligands are summarized and discussed. Their interactions with three types of PPARs are classified by various data from transcript profiles, PPRE reporter in cell line, in silico docking, and gene silencing. The review will contribute to the understanding of the roles of PPARs in the reproductive toxicology of environmental chemicals.